2021
DOI: 10.1212/wnl.0000000000011208
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Small Vessel Disease MRI Features Do Not Improve the Prediction of Stroke Outcome

Abstract: Objective:To determine whether the total small vessel disease (SVD) score adds information to the prediction of stroke outcome compared to validated predictors, we tested different predictive models of outcome in stroke patients.Methods:White matter hyperintensity, lacunes, perivascular spaces, microbleeds, and atrophy were quantified in two prospective datasets of 428 and 197 first-ever stroke patients, using MRI collected 24-to-72 hours after stroke onset. Functional, cognitive, and psychological status were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 47 publications
1
21
1
Order By: Relevance
“…Although other studies have found no incremental discrimination improvement of cerebral small‐vessel disease markers for functional outcome, 35 our study showed that incorporation of those markers modestly improves established mortality risk scores. A review regarding this topic concluded that neuroimaging markers including CBI were poor prognostic markers for several outcomes including long‐term functional outcome 36 .…”
Section: Discussioncontrasting
confidence: 87%
“…Although other studies have found no incremental discrimination improvement of cerebral small‐vessel disease markers for functional outcome, 35 our study showed that incorporation of those markers modestly improves established mortality risk scores. A review regarding this topic concluded that neuroimaging markers including CBI were poor prognostic markers for several outcomes including long‐term functional outcome 36 .…”
Section: Discussioncontrasting
confidence: 87%
“…Similarly, Bu and colleagues [ 61 ] could not identify a connection between SVD radiological markers, such as WMHs, lacunes, and EPVSs and early stroke outcome. Apart from that, in an attempt to evaluate the predictive value of the “brain before stroke”, Coutureau and colleagues [ 72 ] examined whether cerebral SVD parameters, such as WMHs, lacunes, EPVSs, CMBs, cerebral atrophy and the total SVD score would add information to the prediction of early stroke outcome compared to validated predictors, such as age and baseline NIHSS. Even though all cerebral SVD parameters were associated with patient outcome they did not provide significant improvement of early stroke outcome prediction.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with what recently observed in an independent cohort of first-ever stroke patients, although older than those included in our series. 25 Therefore, although subclinical vascular lesions are common incidental findings on MRI brain scans in young patients with ischemic stroke their clinical and therapeutic significance remains uncertain.…”
Section: Discussionmentioning
confidence: 99%